Acral Necrolytic Erythema: A Case Series - Cheekireddy, Sreesha; RM, Kavyadeepu; Sekar, Mohnish (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
It is currently accepted that necrotic acral erythema (NAE) represents a separate clinical entity, unlike earlier when it was a part of necrolytic migratory erythema. It manifests clinically as symmetrically distributed, well-defined, hyperpigmented papules and plaques with thick adherent scales over the dorsum of the feet. According to some theories, the underlying pathogenic mechanism of NAE is hepatic dysfunction leading to metabolic abnormalities such as hypoalbuminemia, hypoaminoacidemia, hyperglucagonemia, and transitory zinc insufficiency. To differentiate NAE from other necrolytic erythemas, a deeper comprehension of the etiopathogenesis and histological characteristics is necessary. Here, we report a case series of patients with necrolytic acral erythema & zinc deficiency, as evaluated, who showed significant improvement with oral zinc supplementation